Analisis Experiential Marketing Berupa Sense, Feel, Think, Act dan Relate serta Pengaruhnya terhadap Kepuasan Pengunjung Taman Rimba Zoo di Kota Jambi - Mustika Mustika; Agesha Marsyaf; Iis Niyati (Ekonomis: Journal of Economics and Business, 2023)
This research is entitled “ Experential Marketing Analysis in the form of Sense, Feel, Think, Act and Relate and their Effects in Visitor Satisfaction at Taman Rimba Zoo in Jambi city”. The objectives of this research are; 1) To find out and analyze the description of sense, feel, think, act, relate and visitor satisfaction at Taman Rimba zoo. 2) to find out and analyze the influence of Sense, Feel, Think, act and Relate on visitor satisfaction at Tamn Rimbo zoo. Based on the research results show that; 1) the results of the descriptive analysis show that sense, feel, think, act, relate and satisfaction are going well and can make a positive contribution to Taman Rimba Zoo in Jambi city. 2) the results of partial hypothesis testing show that the experiential marketing variable consisting of think and act has a positive and significant influence on visitor satisfaction at Taman Rimba Zoo in Jambi city and Simultaneously or together sense, feel, think, act and relate have an effect on visitor satisfaction at Taman Rimba Zoo in Jambi city.